PENEGAKAN HUKUM TERHADAP PELAKU PUNGUTAN LIAR DENGAN MODUS UANG ADMINISTRASI DI KANTOR KECAMATAN RUMBAI BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2001 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Erna Puspita Sari; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One form of corruption that often happens in everyday life is illegal levies. Illegal charges are often conducted in various modes, one of which is administrative money in the management and publication of residence documents in government agencies such as in the Rumbai District Office. Thus, it includes illegal bans and individuals who can be convicted under Law Number 20 Year 2001 Amendment to Law Number 31 Year 1999 concerning the Eradication of Criminal Acts of Corruption. Based on this fact, then there are three formulation of the problem in writing this thesis, namely: First How law enforcement against the perpetrators of illegal levies with the mode of administration money in Rumbai District Office Based on Law Number 20 Year 2001 About Corruption Eradication ?, second, what obstacles in law enforcement against illegal levies in Rumbai District Office ?, third what is the effort done in law enforcement against illegal levies in Rumbai sub-district office ?. The research method in this research is qualitative research method with empirical juridical approach or sociological law research. Data sources are supported by primary and secondary data sources. Data collection techniques used were interviews, questionnaires and literature review. After the data collected then analyzed qualitatively, and draw conclusions with the deductive thinking method of analyzing the problem from the general shape to the special form. From the results of research and discussion it can be concluded that, Law enforcement against the perpetrators of illegal levies by civil servants will be applied Article 12 of Law Number 20 Year 2001 Amendment to Law Number 31 Year 1999 on the Eradication of Corruption but the illegal charges that occurred in the Office District of Rumbai conducted by employees for the sake of personal interest as if it has become a habit. Residents who feel restless but do not report the action make the employees who do it does not have a deterrent effect. The obstacles in law enforcement are the absence of reports from the public, Financial (Finance), Lack of Concern and Awareness of Law Society, Culture and Habit, Lack of cooperation of Regional Supervisory Board and Police Apparatus. Some efforts were made to overcome these obstacles by giving a plea for notification of the prohibition of corruption, socialization of the people of Rumbai Sub-district, and improving the cooperation of the Regional Supervisory Board and the Police Service. Keywords: Law Enforcement-Corruption-Illegal Drawing